Effect of Geranylgeranylacetone on Ultraviolet Radiation Type B-Induced Cataract in Heat-Shock Transcription Factor 1 Heterozygous Mouse. (4th May 2017) - Ogasawara, Satoshi; Hashizume, Kouhei; Okuno, Takashi; Imaizumi, Toshiyasu; Inomata, Yui; Tezuka, Yu; Sanbe, Atushi; Kurosaka, Daijiro
ABSTRACT: Purpose : We investigated whether heat-shock transcription factor 1 (HSF1) was involved in ultraviolet radiation type B (UVR-B)-induced lens opacity (cataract) using HSF1 heterozygous mice. We also examined the effects of geranylgeranylacetone (GGA), an inducer of heat-shock proteins via activation of HSF, on the UVR-B-induced cataract. Material and Methods : Male HSF1 +/– and WT mice were unilaterally exposed to UVR-B (total: 1200mJ) at 16 weeks of age. At 48 h after the last UVR-B irradiation, the lens was isolated and the induction of the cataract was quantified as the cataract area ratio (opacity area/anterior capsule). GGA was orally administered at a dosage of 500 mg/kg once a day for two days before the first UVR-B exposure until the end of the experiment (21days in total). Results : The HSF1 expression was more greatly decreased in the lens from HSF1 +/– mice than in that from WT mice ( p < 0.01). UVR-B exposure could mainly induce cataracts in the anterior capsule in both HSF1 +/– and WT mice, while the opacity of the lens was markedly enhanced in HSF 1+/– mice compared to that in WT mice( p (0.01). GGA treatment could prevent the induction of lens opacity by UVR-B exposure in both WT and HSF1 +/– mice as compared with the non-administration group ( p < 0.01). No obvious alteration by the UVR-B radiation was seen in lens protein levels of αA-crystallin, αB-crystallin, or γ-crystallin with or without GGA administration among all groups of mice. In contrast to the crystallins, the lens protein level of HSP25 was decreased by UVR-B exposure in both HSF1 +/– and WT mice, and was significantly recovered in WT mice by the GGA treatment ( p < 0.01). The induction of HSP25 was suppressed in HSF1 +/– mice compared with that in WT mice. Conclusions : These data suggest that HSF1 plays an important role in the occurrence of UVR-B-induced cataracts, possibly via regulation of HSPs such as HSP25.